Utility of exercise duplex imaging in a rare case of bilateral iliac artery endofibrosis in an ultramarathon runner - Noor Fatima, MBBS; Hamza Hanif, MD; Tram Le, MD; Rachel C. Danczyk, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
External iliac artery endofibrosis is a recognized cause of exertional leg claudication in young, high-endurance athletes. However, significant diagnostic delays often occur owing to the inability of standard testing to replicate exercise-induced symptoms. We present a case of bilateral external iliac artery endofibrosis in an ultramarathon runner who was successfully treated with bilateral external iliac artery patch angioplasty using the great saphenous veins. This case highlights the diagnostic difficulties involved and emphasizes the importance of maintaining a high level of clinical suspicion for iliac artery endofibrosis in athletes who experience exertional lower extremity symptoms.